Effect of dual antiplatelet on recurrent stroke in minor stroke or TIA depends on bodyweight - Ma Y; Liu Y; Xu J; Wang YL; Wang YJ; Du FH (Dove Medical Press, 2018)
Yan Ma,1 Ying Liu,2–5 Jie Xu,2–5 Yilong Wang,2–5 Yongjun Wang,2–5 Fenghe Du1 1Department of Cardiology, Beijing Tiantan Hospital, Capital Medical University, Beijing, China; 2Department of Neurology, Beijing Tiantan Hospital, Capital Medical University, Beijing, China; 3China National Clinical Research Center for Neurological Diseases, Beijing, China; 4Center of Stroke, Beijing Institute for Brain Disorders, Beijing, China; 5Beijing Key Laboratory of Translational Medicine for Cerebrovascular Disease, Beijing, China Objective: To assess whether bodyweight influences the efficacy and safety of dual antiplatelet therapy (DAT) in male patients with minor stroke or transient ischemic attack patients. Materials and methods: All 3,420 male participants coming from the Clopidogrel in High-Risk Patients with Acute Non-disabling Cerebrovascular Events trial were divided into 3 groups based on bodyweight (<65 kg, 65–75 kg, and ≥75 kg). The stroke outcomes included stroke recurrence, combined vascular events, and bleeding events during 90 days of follow-up. The interaction of the treatment effects of DAT among patients with different bodyweight was assessed by Cox proportional hazards models. Results: DAT is superior to mono antiplatelet therapy (MAT) for reducing stroke recurrence among patients with weight <65 kg (5.0% vs 11.7%; hazard ratio [HR], 0.41; 95% CI: 0.22–0.76) and 65–75 kg (6.7% vs 10.8%, HR, 0.62; 95% CI: 0.43–0.89). However, no significant difference was found in stroke recurrence between DAT and MAT in patients with weight ≥75 kg (9.4% vs 11.6%; HR, 0.80; 95% CI: 0.58–1.10). A significant interaction was observed between weight and antiplatelet therapy on stroke recurrence (p<0.05). Similar result was found for combined vascular events. More bleeding events were found in DAT group among patients with weight <65 kg (3.7% vs 2.2%), but with no significant difference. Conclusion: DAT does not show benefit in patients with higher weight, compared with MAT. Bleeding events found in the DAT group were not more than the MAT group among patients with lower weight. Clinical trial registration: URL: http://www.ClinicalTrials.gov. Unique identifier: NCT00979589. Keywords: bodyweight, dual antiplatelet therapy, ischemic stroke, outcomes, TIA